2006
DOI: 10.1021/jf062894y
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution, Complexing Capacity, and Stability of Phosphate−Metal−Humic Complexes

Abstract: Size distribution, maximum complexing ability, and stability constants for phosphate-metal-humic (PO43--M-HA) complexes involving two trivalent (Fe and Al) and five divalent metal (M) bridges (Zn, Cu, Mn, Ca, and Mg) were investigated at the pH values 4, 6, and 8. Results highlighted the existing competition between metal-humic acid (M-HA) aggregation and the formation of PO43--M-HA complexes. However, the fact that only a very low fraction of complexed metal is involved in PO43- fixation seems to be related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 14 publications
6
41
0
Order By: Relevance
“…The presence of this ligand might impede the formation of intermolecular metal bridges among natural chelating molecules, thus allowing the stable complexation of a larger metal concentration as well as the formation of metal‐natural chelates of smaller size. We have observed these mechanisms in studies on the complexation of phosphate by metal‐humic complexes 12, 14, 15…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of this ligand might impede the formation of intermolecular metal bridges among natural chelating molecules, thus allowing the stable complexation of a larger metal concentration as well as the formation of metal‐natural chelates of smaller size. We have observed these mechanisms in studies on the complexation of phosphate by metal‐humic complexes 12, 14, 15…”
Section: Introductionmentioning
confidence: 92%
“…In the case of humic‐related chelates or complexes, the problems of their low efficiency under soil conditions derive from their low average stability and very large size, which cause chelate and metal precipitation in soil 10, 11. A number of studies show that metal complexation by humic systems involves the formation of large molecular aggregates via intermolecular metal bridges 12. This suggests that only a small fraction of metal, that involved in metal bridges, is complexed with high stability, whereas a major metal fraction is associated with molecular aggregation through interactions with low stability 13.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies reported that humic-metal complexes involving many diverse cations were able to complex significant amounts of phosphate in aqueous solutions with pH values ranked between 4 and 8 [40][41][42]. These results also showed that the stability of humic-metalphosphate complexes did not significantly vary with pH [42].…”
Section: Cation Complexing Ability Of Hsmentioning
confidence: 73%
“…Further studies demonstrated that these types of humic-metalphosphate complexes can be obtained in the laboratory [40][41][42][43]. These studies also showed that these complexes were stable and soluble in soil solutions with pH values ranked between 4 and 8 [41,42]. Other studies showed that these humic-metal-phosphate complexes prevented phosphate soil fixation and provided available P to different plant species [46].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 88%
“…As far as the formation of stable and soluble PMHA is concerned, recent studies have described their viability, stability, and solubility in solution, as well as the electronic conditions that favour their formation . However, no information exists about both their dynamics in soil and plant availability in relation to their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%